Evaluation of X-ray Exposure to Radiology Staff in Some Hospitals of Babylon Governorate - Hasan Hussein, Zainab; Abdul Ameer, Nihad; Shakir, Eman (International Journal of Psychosocial Rehabilitation, 2020)
After almost all hospitals used X-rays for medical diagnosis, it became clear that expanded or repeated publicity to this radiation was considered a danger, so it was important to distinguish or measure radiation by devices to protect the medical staff from unnecessary radiation. The aim of this study was to measure the severity of X-rays on the radiologist and calculate the weekly and annual dose equivalent in a clinical imaging radiology department in different Babylon hospitals. Therefore, the purpose of this work is to limit the number of ionization levels in workers and to identify the effects of different parameters on staff dosages. The measurements will be done at three different locations: before and after the protective barrier inside the examination unit, and the third one is outside in the corridor at eight hospitals within the province of Babylon. The distances from the X-ray tube were 0, 20, 40, 60, 80, and 100 cm to the radiologist's position. Determinants of radiation risk include not only radiation dose levels but also clinical workforce ages, intercourse, and their location. These elements can decrease or increase the hazard of publicity.